2021
DOI: 10.3390/molecules26216430
|View full text |Cite
|
Sign up to set email alerts
|

Statistically Optimum HKUST-1 Synthesized by Room Temperature Coordination Modulation Method for the Adsorption of Crystal Violet Dye

Abstract: Due to its excellency and versatility, many synthesis methods and conditions were developed to produce HKUST-1 ([Cu3(BTC)2(H2O)3]n). However, the diversity of HKUST-1 was actually generated both in terms of characteristics and morphologies. Hence, the consistency of HKUST-1 characteristics and morphologies needs to be maintained. The statistical analysis and optimization provide features to determine the best synthesis condition. Here, a room-temperature coordination modulation method was proposed to maintain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…These results are in agreement with those reported in the literature. 38,59–61 The presence of binders was confirmed by their characteristic signals. A weak band at 1043 cm −1 , characteristic of the C–O–C stretching mode of cellulose ethers, 62,63 is observed in the HKUST@MC spectrum with a slight shift in relation to the spectrum of the pure binder (1053 cm −1 ), which can be explained as due to the interactions between the binder and the MOF.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…These results are in agreement with those reported in the literature. 38,59–61 The presence of binders was confirmed by their characteristic signals. A weak band at 1043 cm −1 , characteristic of the C–O–C stretching mode of cellulose ethers, 62,63 is observed in the HKUST@MC spectrum with a slight shift in relation to the spectrum of the pure binder (1053 cm −1 ), which can be explained as due to the interactions between the binder and the MOF.…”
Section: Resultsmentioning
confidence: 95%
“…The HKUST-1 characteristic peaks at 2 θ = 6.9°, 9.5°, 11.6°, 13.4°, 17.5°, and 19.0° are present for all samples. 38,57–59…”
Section: Resultsmentioning
confidence: 99%
“…22 The strong peak observed at 1453 cm À1 was associated with the aromatic CQC stretching vibration. 23 The band at 1115 cm À1 corresponded to OC-OH stretching. 24 Cu-O stretching was observed at 728 cm À1 , which indicated that oxygen was coordinated to the center of copper metal.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is often a discrepancy between different reports on the same MOF structures, which usually arises from different synthesis parameters. For example, the stability of the HKUST-1 framework to 250 °C was reported in [ 10 ] and to 310–330 °C in [ 11 ]. In addition, the prolonged exposition to increased temperature (but in the theoretical range of MOF stability) may result in the slow decomposition of the linker molecules, and finally, the collapse of the framework.…”
Section: Introductionmentioning
confidence: 99%